The assessment of antimalarial drug efficacy. - White, N (2002)
Antimalarial drug efficacy in uncomplicated malaria should be assessed parasitologically in large, community-based trials, enrolling the age groups most affected by clinical disease. For rapidly eliminated drugs, a 28-day follow-up is needed, but, for slowly eliminated drugs, up to nine weeks could be required to document all recrudescences, and, when possible, the drug levels should also be measured. The WHO 14-day assessments are neither sensitive nor specific. In tropical Plasmodium vivax and Plasmodium ovale infections treated with chloroquine, the first relapse is usually suppressed by residual drug levels. A relapse cannot be distinguished confidently from a recrudescence. Host immunity is a major contributor to the therapeutic response, and can make failing drugs appear effective.